2022
DOI: 10.3390/ijerph19020963
|View full text |Cite
|
Sign up to set email alerts
|

The Moderation of Perceived Comfort and Relations with Patients in the Relationship between Secure Workplace Attachment and Organizational Citizenship Behaviors in Elderly Facilities Staff

Abstract: This study focuses on caregivers who work in residential facilities (RFs) for the elderly, and specifically on their organizational citizenship behaviors (OCBs) in relation to their interaction respectively with the overall context (workplace attachment dimension), the spatial-physical environment (perceived environmental comfort), and the social environment (relationship with patients). A sample of health care workers (medical or health care specialists, nurses, and office employees, n = 129) compiled a self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…This could be due to the fact that individuals are supposed to internalize meaningful places which will become an integral part of their identity (Scrima et al, 2021). Consistently, our hypothesized positive relationship between secure workplace attachment and work engagement (H1) is confirmed, also in line with previous research based on the classic attachment theory (Bowlby, 1969), showing that a secure attachment style promotes work performance (Kale, 2020;Ronen & Zuroff, 2017;Vîrgă et al, 2019), extra-role behavior (e.g., organizational citizenship behavior: Little et al, 2011;Nonnis et al, 2022), job satisfaction (Loi et al, 2014;Rioux & Pignault, 2013;Scrima et al, 2019), and protection from burnout symptoms (Pšeničny & Perat, 2020;Scrima et al, 2021), stress (Johnstone & Feeney, 2015) and workaholism (Tziner & Tanami, 2013). Employees who integrate into their identity that IWMs, typical of a secure workplace attachment, will thus experience organizational problems as their ones and will be personally committed to improving the quality of their work.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This could be due to the fact that individuals are supposed to internalize meaningful places which will become an integral part of their identity (Scrima et al, 2021). Consistently, our hypothesized positive relationship between secure workplace attachment and work engagement (H1) is confirmed, also in line with previous research based on the classic attachment theory (Bowlby, 1969), showing that a secure attachment style promotes work performance (Kale, 2020;Ronen & Zuroff, 2017;Vîrgă et al, 2019), extra-role behavior (e.g., organizational citizenship behavior: Little et al, 2011;Nonnis et al, 2022), job satisfaction (Loi et al, 2014;Rioux & Pignault, 2013;Scrima et al, 2019), and protection from burnout symptoms (Pšeničny & Perat, 2020;Scrima et al, 2021), stress (Johnstone & Feeney, 2015) and workaholism (Tziner & Tanami, 2013). Employees who integrate into their identity that IWMs, typical of a secure workplace attachment, will thus experience organizational problems as their ones and will be personally committed to improving the quality of their work.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, satisfying past relationships with places should allow the individual to internalize IWMs characterized by intentions, strategies, and beliefs that can influence the perception of comfort. A recent study found, in fact, a significant positive correlation between secure workplace attachment style and perceived comfort in the staff of elderly facilities (Nonnis et al, 2022). In the light of that, it is expected that: H2: Secure workplace attachment style is positively related to Perceived comfort.…”
Section: Secure Workplace Attachment and Perceived Comfortmentioning
confidence: 94%
See 1 more Smart Citation
“…Employees with insecure workplace attachment styles (i.e., avoidant and preoccupied) have been shown to be more exhausted than others (Scrima et al, 2021). Secure workplace attachment was also found to promote organizational citizenship behaviors in health workers (Nonnis et al, 2022).…”
Section: Workplace Bullying and The Job Demands-resources Modelmentioning
confidence: 97%
“…This association is corroborated by a positive correlation between organizational citizenship performance and organizational climate ( Bahrami et al, 2016 ; Berberoglu, 2018 ). Furthermore, workplace attachment is also connected to helping behavior toward colleagues ( Le Roy and Rioux, 2012 ), civic virtue and altruism ( Nonnis et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%